A cross-sectional study of the association between mobility test performance and personality among older adults. Issue 1 (December 2016) - Agmon, Maayan; Armon, Galit
Abstract Background Falls among the elderly are a major public health challenge. The Timed-Up and Go (TUG) test is commonly used to identify older adults with mobility limitations. This study explored the association between TUG test results and personality among community-dwelling older adults. Methods This cross-sectional study included 85 older adults. Personality was evaluated with the Five Factor Model. Times to complete the TUG as a single task (TUGST) alone and also with an additional cognitive task i.e., dual-task (DT), were recorded. Ordinary least squares OLS regression models were used to examine the associations between personality factors and both single DT TUG. Results Extraversion was found to be inversely associated with time to complete the TUGST (β = -.26, p  < .05). Conscientiousness was inversely associated with TUGDT (β = -.24, p  < .01). Conclusions Findings from this study highlight the relationship between personality and the TUG test. Specifically, older adults with high Extraversion completed the TUGST test more quickly than those who had lower measures of this trait and, people with high Conscientiousness completed the TUGDT tests more quickly. These findings may contribute to early identification of older adults at higher risk from mobility limitations and falls, and to developing personality-tailored interventions for fall prevention.